The Feasibility of the Policy for the Use of Technology Summary of E-Vote Result on the 2019 Election - Ginting, Josep; Sipahutar, Hotnier; Halik, Abdul (Jurnal Bina Praja, 2018)
Problematic manual recapitulation led to the development of the use of e-recapitulation technology. This study aims to determine the feasibility of using e-recapitulation of vote counting in the upcoming 2019 general election. The location of this study was in Pekalongan, Central Java Province (pilot project using e-recapitulation). The method used is the descriptive qualitative method, the sources KPUD officers, Bawaslu officers, the DPRD, and the political unit of the Kesbangpol of Pekalongan. Data collection techniques used were the interview techniques. The technique of data analysis is the inductive basis, i.e., the data collected are discussed, interpreted, and collected in an inductive manner, and draw conclusions from the specific data. Field results show that technology basically e-vote election results recap (in particular _ USSD and DMR) is feasible to be used on the 2019 concurrent election, based on its ability to maintain the integrity of the vote-counting results from the polling stations. Although in the technology itself, the e-recapitulation technology is feasible to be used, it is expected that various problems as identified in this study would occur in the field during the implementation of the technology. Therefore, there needs to be a policy to anticipates the problems that might arise in the use of e-recapitulation technology in the 2019 elections. Such as early communication between the Ministry of Home Affairs and the Central Election Commission to require the use of e-recapitulation in 2019 election, to improve the quality of democracy in Indonesia, as well as to prepare the internet network throughout Indonesia.